Workability's recreation methodic with application of cupping massage and autogenic training of women student teams' basketball players - Zh.L. Kozina; L.V. Kozhuhar; I. N. Sobko; M.A. Vaksler; A.A. Tihonova (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to experimentally subsituate effectiveness of non traditional complex methodic of recreation in female basketball players' training process. Material: 22 basketball players of women student's team participated in the research. Pedagogic testing was conducted by 12 tests in special physical and technical fitness. Psycho-physiological testing was conducted by program PSYCHO-DIAGNOSTIC. Groups were trained by identical programs during 9 weeks. Results: we authors observed increased physical and technical fitness of basketball players. Besides, quantity of mistakes in response to visual irritator reduced. It indirectly witnesses about strengthening of nervous processes. There was registered influence of mind on quality of organism's recreation after physical loads. Conclusions: the authors recommend methodic of cupping massage, combined with autogenic training. Autogenic training implies repeated pronouncing by instructor (or independently by sportswomen) of text, describing coming turn by turn natural images. Peculiarities of massage were influence of massage passes on muscles and ligaments. Cupping massage was used after warming up classic massage techniques.